2016
DOI: 10.22159/ijpps.2017v9i1.15053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Impact of Pharmaceutical Care on Improving Knowledge and Medication Adherence in CKD Patients

Abstract: Objectives: Evaluation of the impact of pharmaceutical care on improving knowledge and medication adherence in Chronic Kidney Disease (CKD) patients.Methods: Patient data were recorded on a data collection form after informed consent. Their knowledge and medication adherence were evaluated by questionnaire and it was quantified. Patients were counselled using patient information leaflets. Re-assessment was made during follow-up.Results: Medication adherence among patients was classified as low, medium and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…Similarly, studies conducted in India that enrolled both pre-dialysis and dialysis CKD patients also reported much higher sub-optimal medication adherence rates ranging from 78.0% to 98.5%. 16 , 29 – 32 Variation in the methods of assessments, study populations, level of information or education received from healthcare personnel and other patient-related factors could account for this difference. Studies have shown that sub-optimal medication adherence is associated with heightened risk for CKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies conducted in India that enrolled both pre-dialysis and dialysis CKD patients also reported much higher sub-optimal medication adherence rates ranging from 78.0% to 98.5%. 16 , 29 – 32 Variation in the methods of assessments, study populations, level of information or education received from healthcare personnel and other patient-related factors could account for this difference. Studies have shown that sub-optimal medication adherence is associated with heightened risk for CKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence shows that pharmacists' interventions, such as education and patient self-management practices among others, are critical for effective management of CKD. 11,12 Systematic reviews and meta-analyses have demonstrated significantly improved BP, renal function, medication adherence, and patient satisfaction among others due to pharmacists' interventions. [13][14][15] Meeting BP targets lower CVD occurrence, [16][17][18] and long-term BP monitoring is critical in hypertension care and may involve home BP monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the pharmacist can positively impact the overall care of CKD patients through the provision of clinical services targeted toward safe and efficacious health outcomes. Available evidence shows that pharmacists' interventions, such as education and patient self‐management practices among others, are critical for effective management of CKD 11,12 . Systematic reviews and meta‐analyses have demonstrated significantly improved BP, renal function, medication adherence, and patient satisfaction among others due to pharmacists' interventions 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of care that respondents the most frequently ranked as excellent were staff attention to dialysis vascular access; caring of nurses; staff responsiveness to pain or discomfort; caring, helpfulness and sensitivity of dialysis staff; and ease of reaching dialysis staff by telephone. The aspects of care least frequently ranked as excellent were information provided when choosing a dialysis modality, ease of seeing a social worker, information provided about dialysis, accuracy of information from nephrologists, and accuracy of nephrologists' instructions 12 .…”
Section: Introductionmentioning
confidence: 99%